Pertumbuhan Mata Tunas Jeruk Keprok (Citrus nobilis) Hasil Okulasi pada Berbagai Media Tanam dan Umur Batang Bawah Rough Lemon (C. jambhiri) - Tatiek Kartika Suharsi; Ananda Dian Puspita Sari (Jurnal Ilmu Pertanian Indonesia, 2013)
The objective of this study was to evaluate keprok (Citrus nobilis) budding seed development on various growing media and age of C. jambhiri rootstock. The design of experiment was complete randomized groups with 2 factors and 3 replications. The growing media consisted of soil, charcoal husk, sheep’s manure, compost, and vermi-compost. Rough lemon citrus rootstock’s age were 8, 11, and 14 months. The results showed that the growing media of soil:charcoal husk:compost or vermicompost mixture of [1:1:1] (v:v:v) was the best media for increasing keprok bud growing. Rough lemon rootstock of 8 and 11 months age were the best rootstock for keprok. Rough lemon rootstock of 14 month age stimulated growth of keprok bud faster than that of 8 and 11 month age of rootstock.